2017
DOI: 10.3389/fmicb.2017.01158
|View full text |Cite
|
Sign up to set email alerts
|

Differential Growth of Francisella tularensis, Which Alters Expression of Virulence Factors, Dominant Antigens, and Surface-Carbohydrate Synthases, Governs the Apparent Virulence of Ft SchuS4 to Immunized Animals

Abstract: The gram-negative bacterium Francisella tularensis (Ft) is both a potential biological weapon and a naturally occurring microbe that survives in arthropods, fresh water amoeba, and mammals with distinct phenotypes in various environments. Previously, we used a number of measurements to characterize Ft grown in Brain-Heart Infusion (BHI) broth as (1) more similar to infection-derived bacteria, and (2) slightly more virulent in naïve animals, compared to Ft grown in Mueller Hinton Broth (MHB). In these studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 102 publications
(240 reference statements)
4
26
0
Order By: Relevance
“…As part of these efforts, we report here that while the choice of culture medium for the aerosolized challenge agent did not affect the survival of unvaccinated rabbits, it did affect the survival of vaccinated rabbits. The latter observations mirror those reported for the intranasal challenge of vaccinated inbred mice (27). The implications of these findings and the impact on conducting pivotal vaccine efficacy studies for tularemia and other high-priority, aerosolized agents are discussed.…”
supporting
confidence: 73%
“…As part of these efforts, we report here that while the choice of culture medium for the aerosolized challenge agent did not affect the survival of unvaccinated rabbits, it did affect the survival of vaccinated rabbits. The latter observations mirror those reported for the intranasal challenge of vaccinated inbred mice (27). The implications of these findings and the impact on conducting pivotal vaccine efficacy studies for tularemia and other high-priority, aerosolized agents are discussed.…”
supporting
confidence: 73%
“…As part of these efforts, we report here that while the choice of culture media for the aerosolized challenge agent did not affect survival of unvaccinated rabbits, it did affect survival of vaccinated rabbits. These latter observations mirror those reported for intranasal challenge of vaccinated inbred mice (26). The implications of these findings and the impact on conducting pivotral vaccine efficacy studies for tularemia and other high-priority, aerosolized agents will be discussed.…”
Section: Introductionsupporting
confidence: 89%
“…We recently reported that LVS-vaccinated, inbred mice survived better if challenged with MHB-grown SCHU S4 than BHI-grown SCHU S4 (26). Using the parameters defined above, we sought to evaluate whether the same pattern of vaccine-mediated protection would be seen in aerosol-challenged outbred rabbits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of several transcriptional regulators, including pmrA, is negatively regulated by RelA/SpoT, and this regulation is independent of the oxidative stress response. An upregulation of pmrA1 has also been reported in bacteria grown in Brain Heart Infusion broth, which mimic intramacrophage growth conditions (27). The upregulated expression of pmrA, specifically in the Δ relA Δ spoT mutant is intriguing and need an additional investigation.…”
Section: Discussionmentioning
confidence: 88%